An idealised assessment of Townsend's outer-layer similarity hypothesis for wall turbulence. (25th February 2014) - Chung, D.; Monty, J. P.; Ooi, A.
Abstract: Direct numerical simulations of turbulent channel flow at the matched friction Reynolds number of 590, comparing the effect of no-slip versus shear-stress boundary conditions, reveal that the outer flow of wall turbulence, in accord with Townsend's outer-layer similarity hypothesis, remains largely independent of the viscous sublayer. First- and second-order statistics, including spectra, agree closely from the buffer region out to the centre of the channel. Higher-order statistics also appear to obey the hypothesised similarity, although the influence of boundary conditions is more pronounced than in the lower-order statistics. The statistical agreement in the outer layer, in spite of the structural differences in the viscous sublayer, support Townsend's idea that the primary effect of the wall is not the no-slip condition, but the impermeability condition imposed by a solid wall.